Pengaruh Pendapatan Asli Daerah, Dana Perimbangan Dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten Dan Kota Di Provinsi Jawa Barat - Ihsan Wahyudin; Hastuti (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The financial performance of local governments is a picture of the success of local governments in managing their regional finances. The purpose of this study was to determine the effect of partially and simultaneous regional original income, balance funds and capital expenditure on the financial performance of district and city local governments in West Java province. This research is a research that uses descriptive quantitative approach. The subjects in this study were 27 districts and cities in the province of West Java. The data used in this study are secondary data in the form of local government financial reports in West Java province in the 2014-2018 fiscal year obtained from the Badan Pusat Statistik and the Badan Pemeriksa Keuangan. Data analysis techniques in this study used simple linear regression analysis and multiple linear regression analysis. The results of the study showed that Original Local Government revenues had a positive and significant effect on the financial performance of local governments. Fiscal Balance Transfer have a positive and significant effect on the financial performance of local governments, Capital Expenditure hasn’t a significant positive effect on the financial performance of local governments. Simultaneously Original Local Government Revenue, Fiscal Balance Transfer and Capital Expenditure have a significant positive effect on the financial performance of local governments.